THE EFFECT OF SELF COMPASSION ON LONELINESS OF FEMALE PRISONERS IN CLASS IIA WOMEN'S PRISON IN MEDAN - Subroto, Mitro; Baskara, Rizky Surya (Universitas Nusa Cendana, 2025)
This study aims to analyse the effect of self-compassion on loneliness in female prisoners at the Medan Class IIA Women's Correctional Institution. In a correctional environment, female inmates often face social and psychological challenges that can exacerbate feelings of isolation and loneliness. Self-compassion, which includes an attitude of self-love and acceptance of one's shortcomings, as well as coping with pain without self-judgement, is expected to help reduce loneliness in inmates. This study used the regression analysis method to examine the relationship between self-compassion and loneliness, the results showed that self-compassion has a significant influence on reducing loneliness levels, with a variance explained of 5.8%. The findings indicate that increasing self-compassion in female prisoners can help them cope better with the challenges of prison, make them more productive, and make them better able to manage emotional distress. This study recommends that prison programmes integrate self-compassion approaches, such as mindfulness training and psychological support, to support the rehabilitation process and improve the mental well-being of female prisoners. This effort is expected to help them face their time in prison more positively and resiliently. Keywords: Self Compassion; Loneliness; Woman Prisoners